Long term survival in patients with human papillomavirus-positive oropharyngeal cancer and equivocal response on 12-week PET-CT is not compromised by the omission of neck dissection. (May 2022) - Zhou, Suyun; Chan, Christopher; Rulach, Robert; Dyab, Hesham; Hendry, Fraser; Maxfield, Carole; Dempsey, Mary-Frances; James, Allan; Grose, Derek; Lamb, Carolynn; Schipani, Stefano; Wilson, Christina; et al.
Highlights: EQR on 12-week PET-CT is a poor predictor of residual disease in HPV-positive HNSCC. 86% of HPV positive equivocal nodal responders had no recurrence on surveillance. Comparable OS between HPV-positive CR & EQR despite omission of immediate ND in 95% Supports the safety of further surveillance following 12-week PET-CT for EQR group. Abstract: Background and Aim: The aim of this study was to evaluate the long-term safety of the omission of immediate neck dissections (IND) in patients with human papillomavirus (HPV)-positive head and neck squamous cell carcinoma (HNSCC) achieving a less than complete nodal response on 12-week FDG PET-CT. Material and Methods: Patients with HPV-positive, node-positive HNSCC that were treated with radical (chemo) radiotherapy (RT) between January 2013 and September 2019 were identified. PET-CT responses were classified as complete (CR), incomplete (ICR) or equivocal (EQR) nodal responses. Clinical outcomes were obtained. Results: 347 patients were identified. Median follow-up was 43.9 (IQR, 30.8–61.2) months. 62.8% (218/347) achieved a CR, 23.4% (81/347) EQR and 13.8% (48/347) ICR nodal response. 70 of 81 (86.4%) patients with an EQR and 25 of 48 (52.1%) with an ICR had no residual disease during follow up (a pathologically negative ND if surgery undertaken or no subsequent neck or distant relapse clinically/radiologically). Median survival of the EQR and CR groups were not reached, and despite the omission of IND in 95% of the EQR group there was no statistically significant differences in overall survival (OS) between the groups, p = 1.0. Median survival of ICR was not reached. However, OS for ICR group was significantly worse than that of CR, and EQR, both p < 0.001. Conclusion: The omission of IND in those achieving an EQR nodal response does not compromise long-term survival. This supports the safety of extended surveillance in patients with HPV-positive disease and an EQR on 12-week FDG PET-CT.